PROYECTOS ESCOLARES EN EL APRENDIZAJE DEL MOVIMIENTO EN UNA DIMENSIÓN CON LOS ESTUDIANTES DE PRIMER AÑO DEL (BGU) PARALELO “D”, DE LA UNIDAD EDUCATIVA PEDRO VICENTE MALDONADO, PERIODO SEPTIEMBRE 2019-FEBRERO 2020 - Villagómez Vallejo, Fernanda Marivel (2020)
The teaching-learning process is undoubtedly the backbone on which the entire educational process rests, developing this process effectively is a very difficult and complex challenge for the teacher, with Project-Based Learning being an optimal possibility for create spaces for active learning that provide students with group participation, active and collaborative participation, an investigative attitude, the ability to conceptualize, the ability to analyze data, the presentation and presentation of school projects, and taking into account The above, it has been seen favorable to carry out the present research work with the fundamental objective of determining the contribution of project-based learning in the Movement in One Dimension; In addition, the first-year students of the (BGU) were considered as a population, and the students of the parallel “D” as a sample. The research design was non-experimental because no documentary, field and cross-sectional variables were manipulated; while the level was descriptive. The data were obtained by means of a survey applied to the students, likewise the observation sheet was used as an instrument and the Microsoft Office Excel software package using descriptive statistics techniques. In this way, it was observed that project-based learning is innovative because it allows the student to remain active in the knowledge process, developing strengths and skills required in the study of the subject of Physics.